Structural integrity of DEMO divertor target assessed by neutron tomography - Minniti, Triestino; Schoofs, Frank; Evans, Llion Marc; Kockelmann, Winfried; You, Jeong-Ha; Lewtas, Heather (Fusion Engineering and Design, 2021)
The divertor target plates are the most exposed in-vessel components to high heat flux loads in a fusion reactor due to a combination of plasma bombardment, radiation and nuclear heating. Reliable exhaust systems of such a huge thermal power required a robust and durable divertor target with a sufficiently large heat removal capability and lifetime. In this context, it is pivotal to develop non-destructive evaluation methods to assess the structural integrity of this component that, if compromised could reduced its lifetime. In this work we have demonstrated for the first time the feasibility of using neutron tomography to detect volumetric defects within DEMO divertor mock-ups with a spatial resolution of the order of hundreds of micrometers. Neutron tomography is applicable for studying complex structures, often manufactured from exotic materials which are not favourable for conventional non-destructive evaluation methods. This technique could be effectively used during research and development cycles of fusion component design or for quality assurance during manufacturing.
Keywords: CuCrZr; Divertor target; Monoblock; Neutron tomography; Non-destructive evaluation; Qualification; Tungsten